Individual and Dyadic Coping and Fear of Progression in Mothers and Fathers of Children with Hematologic Cancer. Issue 3 (13th August 2019) - Clever, Katharina; Schepper, Florian; Maier, Stephan; Christiansen, Holger; Martini, Julia
Abstract : This study investigated the association of individual and dyadic coping strategies with fear of progression (FoP) in mothers and fathers of children with hematologic cancer. Parental couples ( N  = 44) whose children had been diagnosed with hematologic cancer were recruited at a university hospital and a rehabilitation clinic in Germany between 03/2017 and 08/2017. Data included parents' self‐report on FoP (Fear of Progression Questionnaire—parent version, FoP‐Q‐SF/PR), individual coping (Coping Health Inventory for Parents, CHIP‐D), and dyadic coping (Dyadic Coping Inventory, DCI). Statistical analyses were carried out for mothers and fathers individually as well as for parental couples using dyadic data analyses (e.g., actor‐partner interdependence model, APIM). Individual and dyadic coping strategies were significantly correlated with FoP in mothers, but not in fathers. Fathers' evaluation of the couple's dyadic coping significantly predicted mothers' FoP. The more frequent use of familial integration (CHIP‐D FAM) and maintaining social support (CHIP‐D SUP) as well as a better evaluation of their partners' dyadic coping was significantly associated with lower FoP in mothers. Differences in individual and dyadic coping in parental couples were not associated with FoP. Individual and dyadic coping strategies should be addressed in the psychosocial care of mothers and fathers of children with hematologic cancer. Study results support the benefits of involving fathers in psychosocial interventions, for example, in couple‐based interventions that acknowledge interpersonal effects of coping on FoP. Future research should further explore coping strategies applied by fathers of children with hematologic cancer for the regulation of FoP. Abstract : Este estudio investigó la asociación de estrategias de afrontamiento individual y diádico con el miedo a la progresión (FoP por sus siglas en inglés) en madres y padres de niños con cáncer hematológico. Se reclutaron parejas de padres ( N  = 44) cuyos niños recibieron una diagnosis de cáncer hematológico en un hospital universitario y una clínica de rehabilitación en Alemania entre marzo de 2017 y agosto de 2017. Los datos incluyeron autoinformes de los padres sobre FoP (Cuestionario de miedo a la progresión, versión para padres, FoP‐Q‐SF/PR), afrontamiento individual (Inventario de salud de afrontamiento para padres, CHIP‐D) y afrontamiento diádico (Inventario de afrontamiento diádico, DCI). Se realizaron análisis estadísticos para madres y padres de manera individual, así como para parejas de padres usando análisis de datos diádicos, (p.ej., Modelo de interdependencia actor‐pareja, APIM). Las estrategias de afrontamiento individual y diádico tuvieron una correlación significativa con el FoP en las madres, pero no en los padres. La evaluación por los padres del afrontamiento diádico de la pareja predijo significativamente el FoP de las madres. El uso más frecuente de integración familiar (CHIP‐D FAM) y mantenimiento de apoyo social (CHIP‐D SUP), así como una mejor evaluación del afrontamiento diádico de sus parejas se asoció significativamente con un FoP más bajo en las madres. Las diferencias en el afrontamiento individual y diádico en parejas de padres no se asociaron al FoP. Las estrategias de afrontamiento individual y diádico deben ser enfrentadas durante el cuidado psicosocial de madres y padres de niños con cáncer hematológico. Los resultados del estudio respaldan los beneficios de involucrar a los padres en intervenciones psicosociales, es decir, en intervenciones basadas en parejas que reconocen los efectos interpersonales del afrontamiento en FoP. Investigaciones futuras deberán explorar más las estrategias de afrontamiento empleadas por los padres de niños con cáncer hematológico para regular el FoP. Abstract : 本研究调查了血液科癌症儿童患者的母亲和父亲面对病情继续变化的恐惧（FoP）时个人单独应对的策略和夫妻二人相互作用的二元应对策略。 研究对象为在德国的一家大学附属医院和一个康复诊所里就诊被诊断为血液科癌症的孩童的父母们, 一共招募到44对夫妻, 数据采集时间为2017年3月到8月期间。这些数据具体包括家长自己报告的FoP（FoP问卷‐家长版本‐FoP‐Q‐SF/PR), 个人应对(家长应对健康问题策略清单即 CHIP‐D)和二元应对 (夫妻二人应对健康问题清单即DCI)。本研究对母亲和父亲各人单独作了统计学分析, 也对夫妻二人相互作用作了二元数据分析（比如: 主体‐伴侣互相依赖模型, 即APIM）。 个人和夫妻二人应对策略和母亲的FoP有显著性相关性, 和父亲的没有。看父亲对夫妻二人的二元应对的评价就可以预测很多母亲方面的FoP。越多使用家庭凝聚整合功能和维护好社会关系支持（CHIO‐D SUP）加上较好地评估伴侣的二元应对策略都和母亲方面较低的FoP有显著关联性。个人应对和夫妻二元应对之间的差异性和FoP并没有相关联。 在给予血液科癌症儿童患者的母亲和父亲心理社会方面关照时应该考虑到个人应对策略和二元应对策略。本研究的结果证明了父亲在心理社会干预中多起一些作用的好处, 例如在进行伴侣双方为基础的干预时, 意识到家长二人面对FoP的相互之间的影响。未来的研究可以进一步探究血液科癌症儿童患者的父亲在调节FoP时使用的应对策略。